Evaluasi Program Sekolah Lansia Anggrek di Kecamatan Jonggat Kabupaten Lombok Tengah Nusa Tenggara Barat - Setiani, Ermy; Sulaiman, Lalu; Sismulyanto, Sismulyanto (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT This study evaluates the implementation of the Anggrek Elderly School Program in Jonggat District, Central Lombok Regency, West Nusa Tenggara. The program aims to improve the quality of life of the elderly through informal education that promotes a healthy, independent, active, productive, and dignified lifestyle. The study employs a qualitative descriptive approach through interviews, observations, and documentation. The evaluation is conducted based on the dimensions of context, input, process, and output. Findings indicate that the program's conceptual foundation aligns with Indonesia’s national initiative for Elderly-Friendly Communities. However, inconsistent understanding among program managers and a lack of local commitment reduce its effectiveness. In the input aspect, management support from BKKBN is significant, but limited coordination and reliance on the provincial team hinder local capacity development. Other challenges include inadequate facilities and the limited competencies of program administrators. In the process aspect, the formation and preparation stages are not yet optimal, particularly in curriculum development and coordination with local partners. Nevertheless, the implementation stage is relatively well-executed due to participants' enthusiasm, despite challenges such as an excessive number of students and inadequate facilities. Monitoring and reporting through the Golantang application need improvement to provide concrete solutions to existing issues. In the output aspect, the program has successfully improved participants' quality of life, as reflected in enhanced health status and learning achievements. A participant attendance rate of 80% demonstrates high enthusiasm; however, the learning environment is hindered by overcrowding and limited classroom space. Not all participants can yet be categorized as resilient elderly individuals due to the limited learning duration and the absence of an advanced education level. To enhance program success, better coordination between district and sub-district administrators is necessary, along with optimizing the curriculum to meet local needs, improving human resource competencies, and providing more comfortable and adequate learning facilities. Additionally, there is a need for stronger support from local partners and more active community involvement to ensure the program’s sustainability. Keywords: Program Evaluation; Elderly School, Informal Education, Quality of Life, Resilient ElderlyABSTRAK Penelitian ini mengevaluasi pelaksanaan Program Sekolah Lansia Anggrek di Kecamatan Jonggat, Kabupaten Lombok Tengah, Nusa Tenggara Barat. Program ini bertujuan untuk meningkatkan kualitas hidup lansia melalui pendidikan informal yang mendorong gaya hidup sehat, mandiri, aktif, produktif, dan bermartabat. Penelitian menggunakan pendekatan deskriptif kualitatif melalui wawancara, observasi, dan dokumentasi. Evaluasi dilakukan berdasarkan dimensi konteks, input, proses, dan output. Menunjukkan bahwa dasar konseptual program sejalan dengan inisiatif nasional Indonesia Ramah Lansia. Namun, pemahaman yang tidak merata di kalangan pengelola dan kurangnya komitmen lokal mengurangi efektivitas program. Pada aspek input, dukungan manajemen dari BKKBN cukup signifikan, tetapi keterbatasan koordinasi dan ketergantungan pada tim provinsi membatasi pengembangan kapasitas lokal. Tantangan lain meliputi keterbatasan fasilitas dan kompetensi pengelola program. Pada aspek proses, tahap pembentukan dan persiapan belum optimal, terutama dalam pengembangan kurikulum dan koordinasi dengan mitra lokal. Meskipun demikian, tahap pelaksanaan berjalan cukup baik berkat antusiasme peserta, meskipun dihadapkan pada kendala jumlah siswa yang terlalu banyak dan fasilitas yang kurang memadai. Proses pengawasan dan pelaporan melalui aplikasi Golantang perlu ditingkatkan agar dapat memberikan solusi konkret terhadap kendala yang ada. Padaaspek output, program berhasil meningkatkan kualitas hidup peserta, dengan hasil yang menunjukkan peningkatan status kesehatan dan capaian pembelajaran. Tingkat kehadiran peserta yang mencapai 80% mencerminkan antusiasme yang tinggi, tetapi suasana belajar terhambat oleh jumlah siswa yang terlalu besar dan keterbatasan ruang belajar. Belum semua peserta dapat dikategorikan sebagai lansia tangguh, karena waktu pembelajaran yang terbatas dan belum adanya jenjang pendidikan lanjutan. Untuk meningkatkan keberhasilan program, diperlukan peningkatan koordinasi antara pengelola di tingkat kabupaten dan kecamatan, optimalisasi kurikulum yang sesuai dengan kebutuhan lokal, peningkatan kompetensi sumber daya manusia, dan penyediaan sarana pembelajaran yang lebih nyaman dan memadai. Selain itu, implikasi perlu adanya penguatan dukungan dari mitra lokal dan pelibatan komunitas secara lebih aktif untuk keberlanjutan program. Kata Kunci: Evaluasi Program, Sekolah Lansia, Pendidikan Formal, Kualitas Hidup, Lansia Tangguh.